Pengaruh Literasi Keuangan Syariah Dan Mental Accounting Terhadap Perilaku Keuangan Generasi Z Dalam Membangun UMKM (Studi Kasus Pelaku UMKM Halal Kota Medan) - Chica Febrian Syaputri; Riyan Pradesyah (Yayasan Rahmat Islamiyah, 2023)
The purpose of this study is to find out whether business owners or MSME actors, especially in the Z generation, understand Islamic financial literacy in running their business and apply mental accounting as a reference for developing their business so that it is more advanced in the future. The method used in this study is a quantitative approach with data collection techniques by distributing questionnaires and data analysis techniques using multiple linear regression, classical assumption testing, hypothesis testing and the coefficient of determination with the SPSS v 23 application. The results show that Islamic financial literacy has a significant value of 0.102 > 0.05 and a positive β value of 0.088. This shows that the Islamic financial literacy variable on Generation Z financial behavior in developing UMKM has an insignificant effect, while mental accounting has a significant value of 0.00 <0.05 and a β value of 0.502. This shows that the mental accounting variable has a significant effect on the financial behavior of Generation Z in building UMKM. When viewed from the Adjusted R square value of 0.284, it indicates that Islamic financial literacy (X1), mental accounting (X2), explains the dependent variable of financial behavior for generation Z (Y) of 28.4% meaning Islamic Financial Literacy (X1), Mental Accounting (X2), has a proportion of influence on the Financial Behavior of Generation Z (Y) in building UMKM of 28.4% and the remaining 71.6% is influenced by other variables.